THE ROLE OF THE LIBRARY IN THE FORMATION OF INCLUSIVE COMPETENCE OF FUTURE TEACHERS: RELEVANCE, DIRECTIONS, EXPERIENCE - BILOUS, Valentina S.; BROVCHAK, Liudmyla S. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. The article is aimed at reviewing the current state of inclusion implementation in Ukraine and the role of university libraries in these processes. Methods. The research was conducted by analyzing the world literature on educational practices of development and implementation of inclusion and experience of the library of Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University (VSPU) in creating inclusive library space. Results. The term "inclusive education" is explained and the factual basis of the importance of training highly qualified teachers in the conditions of inclusive education is expanded. The essence of inclusive teacher competence as a scientific category is analyzed. Emphasis is placed on the experience of the VSPU library in creating an inclusive library space. It is proved that the library, using various forms and methods of work, promotes the introduction of the latest educational standards, among which is the inclusive education. The main directions and aspects of the implementation of the inclusive project "Library without Borders" are highlighted. Conclusions. Ukrainian educational institutions take an active part in inclusive education practices. In these processes, the university library is an important link in providing inclusive education. The necessity of supplementing the further strategy of the library activity with the direction of formation of inclusive space and inclusive library is determined.